CASTLEMAN'S DISEASE IN THE CLINIC OF MAXILLOFACIAL SURGERY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Angiofollicular hyperplasia of the lymph nodes was first described by Benjamin Castleman in 1954, when solitary mediastinal hyperplasia of the lymph nodes was detected in a patient [3]. It is often not accompanied by systemic manifestations. A.R. Keller et al. (1972) classified two histological variants of the disease: hyaline-vascular, occurring in 91% of cases, and plasma cell variant. According to the authors, in 70% of cases the tumor was localized in the chest, in 15% of cases the tumor was localized in the tonsils, lymphoid tissue of the nasopharynx and tongue, in 11% - in the retroperitoneal space, in 4% of cases in the peripheral lymph nodes. The hyaline-vascular type of lymphoma B occurs in 90% of cases, is localized in the neck and is equally common in both sexes [2]. The information we have collected about the pathology has now allowed us to distinguish three morphological variants of Castleman's disease: hyaline-vascular, plasma cell and mixed cell [1]. According to E.K. Egorova, the hyaline-vascular variant occurs in 48.7% of patients, plasma cell - in 23.7% and mixed cell - in 27.6% of patients. Castleman's disease is divided into local and generalized (multicentric). Quite recently, a "subvariant" of generalized Castleman's disease has been described, known as the plasmablastic variant of Castleman's disease, which is the most aggressive. It was first described in a group of patients whose disease was accompanied by the presence of POEMS syndrome. Subsequent research showed that this variant is associated with herpes virus type 8 (HHV8) and the development of plasmablastic lymphoma [1]. Manifestations of Castleman's disease on the face or neck are a reason for oncological alertness.